Zhulavska O., Yehorova A. Continuity in Teaching of Foreing Languages in General Education Schools - O. O. Zhulavska; A. Yehorova (Philological Treatises, 2020)
Nowadays the language learning issue is especially acute, therefore in the context of educational system reforming, consolidated efforts are directed to determine the most perfect and qualitative way of foreign language teaching. To make language learning the most effective, in the educational system continuity must be facilitated and achieved. Continuity is manifested in the sequence and systematic arrangement of the educational material, through the connection and coordination of the stages of teaching and educational work, which is ensured in the transition in the narrow sense from one activity to another, and on a larger scale from one academic year to the next year, from one level to another. Ensuring of continuity in the teaching process is a prerequisite for comprehension of the learned material at a deeper level, reinforcement of the gained knowledge by newly received information, the new relationships disclosure, what gradually results in increasing the quality of knowledge, skills and abilities, improving the level of a foreign language mastery and broadening the total stock of the background knowledge. The article investigates continuity, as one of the compulsory principles of foreign language teaching and learning in general education schools. The main focus is on the research concerning implementation of continuity principle during transition from primary to secondary school. Analysis of the educational system has determined that the principle of continuity in foreign language teaching is often negated and unimplemented during transition from primary to secondary school. As a consequence, a significant quantity of problems is originated in the educational process. It causes the necessity to elaborate ways of solving problems and to implement them as a matter of actual practice.